Prevalence of Heart Disease of Elementary Schoolchildren in a Well-To-Do Population Group, Jakarta 1973 - Maemunah B. Affandi; L.A. Tamaela; R. Widodo Talogo (Paediatrica Indonesiana, 1979)
This study, using as the screening method the presence of heart murmurs, yielded only 28 suspected cases of heart disease. Eight out of the 28 cases were definitely heart disease cases. Two with acquired heart disease (mitral insufficiency) and six with congenital heart disease (4 ventricular septal defect, one atrial septal defect, one patent ductus arteriosus). Growth retardation was observed in 7 children regarding their heights and weights which were less than the lower limit for the normal heights and weights for schoolchildren in Jakarta.